Psychological and Social Gratification Factors Related to Pathological Gaming among Undergraduate Students - Ng, You Ming (2011)
Playing video games is a familiar form of entertainment which is well supported by most of the age groups. In fact, it has become a part of daily life activity of most contemporary youth nowadays. However, many recent researches have shown that this type of pastime activity can bring about a number of negative physical and emotional consequences to the gamers. The main objective of the current study was to identify the psychological and social gratifications that are related to video game playing, specifically pathological gaming among undergraduate students. Cluster sampling approach was used and a total of 255 questionnaires were collected from a cross-sectional data collection. The results of Pearson correlation have indicated that all the seven psychological gratification and three social gratification factors were significantly correlated with pathological gaming. The average amount of playing time is 10.66 hours per week and about 14% of respondents showed moderate to high level of pathological gaming symptoms. Besides, stepwise multiple linear regression further indicated three out of the ten predictors significantly predict pathological gaming and about 52% variance of pathological gaming was explained by three factors, namely Companionship, Competition and Entertainment & leisure. As a conclusion, the present study confirms the validity of uses and gratification theory as a process leading to pathological gaming, implying that individuals with pathological usage of video games are influenced by their inner desires, inner conflicts, negative self-evaluations, and consequent negative emotions. Hence, they tend to indulge in video games, which provide them with immediate satisfaction.